The experiences of women with maternal near miss and their perception of quality of care in Kelantan, Malaysia: a qualitative study - Mohd Noor Norhayati; Nik Hussain Nik Hazlina; Ab Razak Asrenee; Zaharah Sulaiman (BMC, 2017)
Abstract Background Maternal mortality has been the main way of ascertaining the outcome of maternal and obstetric care. However, maternal morbidities occur more frequently than maternal deaths; therefore, maternal near miss was suggested as a more useful indicator for the evaluation and improvement of maternal health services. Our study aimed to explore the experiences of women with maternal near miss and their perception of the quality of care in Kelantan, Malaysia. Methods A qualitative phenomenological approach with in-depth interview method was conducted in two tertiary hospitals in Kelantan, Malaysia. All women admitted to labour room, obstetrics and gynaecology wards and intensive care units in 2014 were screened for the presence of any vital organ dysfunction or failure based on the World Health Organization criteria for maternal near miss. Pregnancy irrespective of the gestational age was included. Women younger than 18 years old, with psychiatric disorder and beyond 42 days of childbirth were excluded. Results Thirty women who had experienced maternal near miss events were included in the analysis. All were Malays between the ages of 22 and 45. Almost all women (93.3%) had secondary and tertiary education and 63.3% were employed. The women's perceptions of the quality of their care were influenced by the competency and promptness in the provision of care, interpersonal communication, information-sharing and the quality of physical resources. The predisposition to seek healthcare was influenced by costs, self-attitude and beliefs. Conclusions Self-appraisal of maternal near miss, their perception of the quality of care, their predisposition to seek healthcare and the social support received were the four major themes that emerged from the experiences and perceptions of women with maternal near miss. The women with maternal near miss viewed their experiences as frightening and that they experienced other negative emotions and a sense of imminent death. The factors influencing women's perceptions of quality of care should be of concern to those seeking to improve services at healthcare facilities. The addition of a maternal near miss case review programme, allows for understanding on the factors related to providing care or to the predisposition to seek care; if addressed, may improve future healthcare and patient outcomes.